Hierarchical Micro-Nano Topography Promotes Cell Adhesion and Osteogenic Differentiation via Integrin α2-PI3K-AKT Signaling Axis - Zheng, Huimin; Tian, Yujuan; Gao, Qian; Yu, Yingjie; Xia, Xianyou; Feng, Zhipeng; Dong, Feng; Wu, Xudong; Sui, Lei (Frontiers in Bioengineering and Biotechnology, 2020)
Surface topography dictates important aspects of cell biological behaviors. In our study, hierarchical micro-nano topography (SLM-AHT) with micro-scale grooves and nano-scale pores was fabricated and compared with smooth topography (S) and irregular micro-scale topography (SLA) surfaces to investigate mechanism involved in cell-surface interactions. Integrin α2 had a higher expression level on SLM-AHT surface compared with S and SLA surfaces, and the expression levels of osteogenic markers icluding Runx2, Col1a1 and Ocn were concomitantly upregulated on SLM-AHT surface. Moreover, formation of mature focal adhesions were significantly enhanced in SLM-AHT group. Noticablely, silencing integrin α2 could wipe out the difference of osteogenic gene expression among surfaces with different topography, indicating a crucial role of integrin α2 in topography induced osteogenic differentiation. In addition, PI3K-AKT signaling was proved to be regulated by integrin α2 and concequently participate in this process. Taken together, our findings illustrated that integrin α2-PI3K-AKT signaling axis plays a key role in hierarchical micro-nano topography promoting cell adhesion and osteogenic differentiation.